ENGAGING STUDENTS IN READING BY ANALYZING CHARACTERS AS A PART OF EXTENSIVE READING ACTIVITY - Eros Meilina Sofa (Universitas Muria Kudus, 2019)
This article discusses about character analysis of a story as a part of Extensive Reading to engage students in reading activity. The writer used qualitative approach to conduct this research by analyzing their works and arguments after the task given, and there were 95 students of English Education Department as the participants. In order to get the data, there were two main sources, the students’ analysis and their written comments on the work. To maintain the concept of Extensive Reading, the students had to read the story and gave their analysis freely on a paper. They also had to write their comment toward the story in several sentences. The result revealed that students could express their ideas and creativity on the paper as well as their capability in creating English sentences. Besides, they could increase their self-confidence because of their ability in reading and analyzing the English story.